The malleability of attentional capture. Issue 9 (21st October 2021) - Zhang, Han; Abagis, Tessa R.; Jonides, John
ABSTRACT: We suggest that consideration of trial-by-trial variations, individual differences, and training data will enrich the current framework in Luck, S. J., Gaspelin, N., Folk, C. L., Remington, R. W., & Theeuwes, J. (2020. Progress toward resolving the attentional capture debate. Visual Cognition, 1–21. https://doi.org/10.1080/13506285.2020.1848949). We consider whether attentional capture is modulated by trial-by-trial fluctuations of attentional state and experiences on the previous trial. We also consider whether individual differences may affect attentional capture while highlighting potential challenges in using the colour-singleton task to measure individual differences. Finally, performance in the colour-singleton task can be modified dramatically with practice but the underlying mechanisms are not entirely clear. Understanding the malleability of attentional capture may broaden the current framework and resolve outstanding questions.